PENGARUH CORPORATE GOVERNANCE PERCEPTION INDEX TERHADAP KINERJA PERUSAHAAN (Pada Perusahaan Yang Terdaftar Di BEI Periode 2013-2015) - Fitri Yulita Sari (e_Jurnal Ilmiah Riset Akuntansi, 2017)
ABSTRACTThis study aims to examine the influence of corporate governance perception index on theperformance of companies listed on the stock exchange Indonesia. Population in this penlitian is allcompanies listed in stock exchange indonesia period 2013-2015. The selection of samples wasconducted based on purposive sampling method, so that obtained the sample of 13 companies. Thedata analysis technique used is multiple linear regression analysis, with data processing using SPSSversion 16.0. The results of this study indicate that the performance of companies in the measured byusing ROE have a significant positive effect on corporate governance perception index, but theperformance of the company measured using tobins'q showed a significantly negative results tocorporate governance perception index.Keywords : Corporate goverance perception index, ROE, Tobins’Q, performance of companies